Faktor-Faktor Yang Berhubungan Dengan Kelelahan Kerja Pada Pekerja Penyapu Jalan Di Kota Surakarta - Sumardiyono; Sherina Chafiidhiya Rochmah; Seviana Rinawati (Sekolah Vokasi, Universitas Sebelas Maret, 2023)
Street sweepers are workers under the Surakarta Environment Agency who focus on cleaning matters in the city area. The main task of a street sweeper is to clean up trash around the sidewalks, slow lanes, and along the main streets in the morning and evening. This can cause workers to easily feel tired. This research is quantitative research using analytic methods with a cross-sectional study design. The research population consisted of 220 street sweepers with a sample of 140 respondents. Sampling using a Simple random sampling technique. Data analysis techniques used the Somers'd test for bivariate tests and Ordinal Logistic Regression tests for multivariate tests. Somers'd correlation results showed that there is a significant relationship between the variables age (p= 0.000), work period (p= 0.000), sleep quality (p= 0.000), and workload (p= 0.000) on fatigue. Meanwhile, breakfast habits (p = 0.097) did not have a significant relationship with fatigue. The results of the Ordinal Logistic Regression test showed that the variable most related to fatigue is workload (OR = 25.305).